MEMBANGUN HUBUNGAN SOSIAL PADA SISWA SMA NEGERI 1 BATANG KABUPATEN JENEPONTO, SULAWESI SELATAN - Fakhri, Nurfitriany (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Â SMA Negeri 1 Batang Â Jeneponto, as an IbM activity partner, have problems related to negative behavior. The observations and interviews conducted with a number of students at SMA Negeri 1 Batang, have shown that many students frequently violated the school rules. In the process of building good relationships with others, there is a section which plays an important role, namely self-control. The solutions offered in the process of this service activities (IbM) performed in several methods such as Focus Group Discussion (FGD), varied lectures, role play and games. This method aims to improve positive thinking in building social relationships in students. As a result of these service activities, students can understand the potential of social intelligence, so that it can be applied in interacting with peersÂ Kata kunci: Self-control, Focus Group Discussion, Lectures, Role play, Games